The “Novel” of Letters by Adolfas and Jonas Mekai: a Person and Place of a Lifeworld - Jakaitė, Dalia (Acta humanitarica academiae Saulensis, 2025)
The book Jonas ir Adolfas Mekai. Gyvenimo lai(š)kai, published in 2020, is not the first book co-written by Mekai brothers. In 1947, a collection of fairy tales, Knyga apie karalius ir žmones, was published. Another creative context is also important for understanding the letters: books by Jonas Mekas Semeniškių idilės, Dienų raštai, films, etc. The letters of Adolfas and Jonas Mekai are another monument to Semeniškiai (a village in Biržai district), at the same time showing the significance of another place in the consciousness of the creators. The aim of this article is to discuss the book of letters of Jonas and Adolfas Mekai by revealing the specifics of local experience in the consciousness of two brothers and other persons involved in communication with them, showing their significance in the history of Semeniškiai myth. For the methodological perspective, the social phenomenology of Alfred Schütz and his conception of the living world were chosen. When reading letters, the importance of space is primarily determined by the book compiler’s special attention to the visual and sensory expression of the publication: the pursuit of authentic reading, the abundance of photographs and other images. Almost every letter begins and ends with Semeniškiai, which face is showed up through the interaction of certain actions, persons, specific local realities and things. One letter from Adolfas Mekas and one of the strongest representations of Semeniškiai reflect on the ambiguous place of memories in the experience of space and place, highlighting the importance of “my” and “other” body, actions of a certain person in local identity. To understand a place, the writer’s attention is important not only to specific realities, but also the openness to the world, the ability to take root in any place. Although the book does not contain the letters of the mother, her figure is formed from the memories of one or another addressee, the answer to her questions, retellings of her stories, etc. By allowing different storylines to unite, the mother becomes one of the most striking “characters” in this epistolary “novel”. Such things as a specific value field of writers, a complicated post-war period, a narrative of an artist who is modern and at the same time rooted in certain traditions, could appear only in her presence.